Cultural integration has obtained a considerable importance in the research literature of English language teaching and learning. Since testing, as an assessment instrument, is an essential part of ELT it can also be exposed to analysis for cultural i - Ali Abdulridha Obaid (Journal of College of Education, 2022)
Cultural integration has obtained a considerable importance in the research literature of English language teaching and learning. Since testing, as an assessment instrument, is an essential part of ELT it can also be exposed to analysis for cultural integration.  In Iraq, Ministry of Education yearly conducts two national examinations (NEs) for both the third intermediate and sixth preparatory classes. To the knowledge of the researcher, culture incorporation in the NEs of Iraq has scarcely addressed in the available literature. The aim of this paper is to discover the cultural bias through finding out the dominant cultural type(s) in a sample of national exams for the sixth preparatory classes. A qualitative research method based on quantifying the frequency occurrences of the cultural representations is followed. Deductive content analysis is employed to work on a primary data of questions’ papers of the NEs. The occurrences are classified in accordance to Aliakbari’s (2004) typology in terms of source, target, international and neutral types of culture. Results indicate that the local culture predominates showing an obvious bias. The study is significant since it is an evaluative study in the Iraqi EFT context, as evaluation is supposed to be an on-going process necessary in any ELT context, providing recommendations to the test designers in relation to integrating culture in language testing.